Cyanide poisoning from an alternative medicine treatment with apricot kernels in a 80-year-old female. - Drankowska, Justyna; Kos, Michał; Kościuk, Andrzej; Tchórz, Michał (Journal of Education, Health and Sport, 2018)
Introduction: Amygdaline, one of the most common cyanogenic glycosides, is present in the seeds and fruit pits of Prunus species. The excessive administration of this glycoside might lead to cyanide poisoning. Aim: The aim of the study is to depict the risk associated with apricot kernels ingestion on the base of the case report. Methods: The analysis of the patient’s medical history and the review of available literature. Results: 80- year- old female with the medical history of papillary thyroid cancer was admitted to the toxicology department due to accidental cyanide poisoning. The patient consumed extract consisted of milled apricot kernels, then suffered from dyspnea, vertigo and vomiting. After that, she lost consciousness. Lactic acidosis, highly specific for cyanide intoxication, was diagnosed during hospitalization. The patient was treated with fluid and steroid therapy, sodium bicarbonate and supplemental oxygen. On the 3rd day of stay, the patient was discharged with recommendation of control in toxicological clinic. Conclusions: Initial symptoms of cyanide poisoning are not specific, therefore it is worth taking this poisoning into account in differential diagnosis, especially in oncological patients or in children.